Factors related to the return to work of head and neck cancer patients diagnosed between 2004-2011 in Belgium: a multivariate Fine-Gray regression model analysis - Maxim Van den Broecke; Sarah de Jong; Katrien Vanthomme; Régine Kiasuwa Mbengi; Christophe Vanroelen (BMC, 2024)
Abstract Background This study aims to identify the key factors that underlie the return to work (RTW) of head and neck cancer (HNC) patients in Belgium. Methods We used data from the EMPCAN database linking data from the Belgian Cancer Registry and the Crossroads Bank for Social Security. We selected HNC patients aged 18-60 at diagnosis who became inactive on the labour market during the follow-up time observed (n = 398). Fine-Gray regression models were used to examine associations between clinical, socio-demographical and work-related factors and RTW over a follow-up of almost 8 years (2004-2011). Results The overall RTW was 21.6%. Stage IV at diagnosis and the use of chemoradiation were associated with a decreased RTW probability but this effect was attenuated by age-adjusted analyses. Multivariate analysis shows that the probability of RTW decreases with age and depends on the household composition. Patients who live alone (SHR 2.2, 95% CI 1.0 - 4.5) and patients who live with another adult and child(ren) (SHR 2.1, 95% CI 1.1 - 4.0) are more likely to RTW than patients who live with another adult without children. Conclusions The cumulative incidence of RTW in HNC patients is associated with age and household composition but not with treatment modalities or stage. In future research, this model could be applied to larger cancer patient groups for more accurate estimations. These insights are of importance to better support patients and for informing tailored policy measures which should take into account the sociodemographic profile of HNC patients to tackle societal and health-related inequities and burden of work inactivity.